ACTIVITY OF THE MINISTRY OF TRADE AND SUPPLY IN BORDER TRADE WITH ALBANIA 1945-1946 (Heritage, 2025)
Yugoslav-Albanianeconomic relations developed intensively in the 1920s and 1930s. The twoneighboring states organized trade and border traffic, given the fact that thepopulation on both sides of the border line depended on each other for trade inessential items. After the end of World War II, the previous agreements ontrade and the circulation of goods were mostly accepted. The Yugoslav side soughtto bind Albania to itself and tear it away from, primarily, Italian influence.Economic cooperation on the Yugoslav side implied the position that Albania wasan area of special interest. Restoring economic ties with Albania, providing personnel assistance,and charting the course of Albanian foreign trade were priorities forYugoslavia.The problems that the Yugoslav authorities,primarily the Ministry of Trade and Supply, encountered in border trade werethe undefined and often uncontrolled crossing of so-called rationed goods,which gave room for smuggling and speculation. The Ministry of Trade and Supplymanaged to regulate the circulation of rationed goods, balancing the legalframework and the needs of the local population, involving other competentministries, as well as republican authorities, in the implementation of themeasures.
Keywords: Democratic Federal Yugoslavia (Federal People's Republic of Yugoslavia), Albania, border traffic, Ministry of Trade and Supply